MENINGKATKAN KEMAMPUAN TIMANG-TIMANG BOLA SEPAK TAKRAW MELALUI PERMAINAN KASKRAW PADA SISWA KELAS V SD NEGERI GENTING 01 KECAMATAN JAMBU KABUPATEN SEMARANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This research ai ms to see t he improvement of the student s' takraw juggling ability through the implementationof kaskraw game. This research was an action research which conducted collaborativel y and part icipat ory. This research was conduct ed in two cycles which one cycle was for one meeting wit h time all ocat i on 105minut es. The subject of this research was the f if t h grade students of SD N genting 01, Jambu dist rict,Semarang regency in academic year 2012/2013. The subj ect of the research was the fifth grade st udents at SDN Gent ing 1. The subj ect was 26 st udents consist of 15 male and 11 female students. In t hi s research, the dat acoll ection techniques that being used were observat ion and documentat ion. The data analysis technique thatbeing used in t his research was desciptive percentage. The target of compl et eness crit eria of takraw j ugglinglesson was 75%. In the f irst cycl e, the percentage of the student s' compl eteness only 38,46. Af t er some correct ion,in t he second cycle, the percentage reached 76,92%. According to the result , this research can be catagorized assuccessful research.